Relaxation of peptidoglycan cross-linking promotes Helicobacter pylori’s helical shape and stomach colonization - Sycuro, Laura K. (2010)
The mechanisms by which bacterial cells generate helical cell shape and its functional role are poorly understood. Helical shape of the human pathogen Helicobacter pylori may facilitate penetration of the thick gastric mucus where it replicates. We identified four genes required for helical shape: three novel LytM peptidoglycan endopeptidase homologues (csd1–3) and a ccmA homologue. Surrounding the cytoplasmic membrane of most bacteria, the peptidoglycan (murein) sacculus is a meshwork of glycan strands joined by peptide cross-links. Intact cells and isolated sacculi from mutants lacking any single csd gene or ccmA formed curved rods and showed increased peptidoglycan cross-linking. Quantitative morphological analyses of multiple-gene deletion mutants revealed each protein uniquely contributes to a shape-generating pathway. This pathway is required for robust colonization of the stomach in spite of normal directional motility. Our findings suggest that the coordinated action of multiple proteins relaxes peptidoglycan cross-linking, enabling helical cell curvature and twist.